Thermoset nanocomposites for engineering applications - Kotsilkova, Rumiana; Pissis, Polycarpos (Smithers Rapra Technology, 2007)
Thermoset nanocomposites represent a new technology solution. These new formulations benefit from improved dimensional/thermal stability, flame retardancy and chemical resistance; and have potential applications in marine, industrial and construction markets. This book helps to answer questions related to the design of nanocomposites by controlling the processing technology and structure. The book is addressed not only to researchers and engineers who actively work in the broad field of nanocomposite technology, but also to newcomers and students who have just started investigations in this mul.